Design and fabrication of recyclable and reshape vitrified elastomer reinforced with renewable cellulose nanocrystal. (June 2022) - Gao, Mingxing; Wang, Yachen; Li, Sai; Liu, Jun; Feng, Anchao; Zhang, Ganggang; Zhang, Liqun
Abstract: Developing the recyclable elastomeric vitrimer with dynamic covalent bonds is a very promising strategy to alleviate the burden of traditional vulcanized rubber materials on the environment. In this work, we proposed to introduce epoxidized soybean oil (ESO) as a cross-linking agent into carboxyl nitrile butadiene rubber (XNBR)/TEMPO-oxidized cellulose nanocrystals (TO-CNC) composites, and successfully prepared ESO-cured XNBR/TO-CNC elastomeric vitrimer with dynamic β-hydroxyl ester bonds, which are formed between the epoxy group of ESO and the carboxyl group of XNBR or TO-CNC. The TEMPO oxidation of CNC is validated by a series of characterizations such as FTIR, conductometric titration, and element analysis. The formation of the β-hydroxyl esters is as well evidenced by the FTIR analysis and the curing curves. Interestingly, the TO-CNC exhibits good dispersion in the composite, and a remarkable mechanical reinforcement is observed for ESO-cured XNBR/TO-CNC elastomer, for instance, the tensile strength of the composite with 15 phr TO-CNC was 2.4 times greater than that of the unfilled sample. Moreover, this composite as well shows good reshaping capability and reprocessability. Generally, this work offers a novel approach to preparing green cross-linked elastomer/bio-based CNC composites that can potentially overcome the bottleneck of the non-recycling of traditional vulcanized rubber. Graphical abstract: Image 1 Highlights: The use of cellulose nanocrystals as fillers is more environmentally friendly than other inorganic fillers. Utilizing ESO as a cross-linking agent to bridge the rubber matrix and the nano-filler can significantly broaden the application of ester exchange bonds. The vitrimer composites can be reshaped and reprocessed.